An adaptable integrated modelling platform to support rapidly evolving agricultural and environmental policy - Harrison, Paula A.; Beauchamp, Kate; Cooper, Joe; Dickie, Ian; Fitch, Alice; Gooday, Richard; Hollaway, Michael; Holman, Ian P.; et al., (Elsevier, 2023)
he utility of integrated models for informing policy has been criticised due to limited stakeholder engagement, model opaqueness, inadequate transparency in assumptions, lack of model flexibility and lack of communication of uncertainty that, together, lead to a lack of trust in model outputs. We address these criticisms by presenting the ERAMMP Integrated Modelling Platform (IMP), developed to support the design of new “business-critical” policies focused on agriculture, land-use and natural resource management. We demonstrate how the long-term (>5 years), iterative, two-way and continuously evolving participatory process led to the co-creation of the IMP with government, building trust and understanding in a complex integrated model. This is supported by a customisable modelling framework that is sufficiently flexible to adapt to changing policy needs in near real-time. We discuss how these attributes have facilitated cultural change within the Welsh Government where the IMP is being actively used to explore, test and iterate policy ideas prior to final policy design and implementation.
Keywords: Integrated modelling; Stakeholders; Co-creation; Trust; Transdisciplinarity; Policy support